2009
DOI: 10.1073/pnas.0904082106
|View full text |Cite
|
Sign up to set email alerts
|

Using a functional enzyme model to understand the chemistry behind hydrogen sulfide induced hibernation

Abstract: The toxic gas H2S is produced by enzymes in the body. At

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
142
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(149 citation statements)
references
References 39 publications
3
142
0
1
Order By: Relevance
“…This notion is consistent with previous studies indicating that pharmacologic inhibition of HO increases basal O 2 consumption in the liver (52) and that an increase in endogenous CO, by enzyme induction inhibits cellular respiration through its inhibitory effect on cytochrome c oxidase (53). H 2 S also might modulate mitochondrial respiration through reversible inhibition of cytochrome c oxidase (54); however, at least in the present study, basal H 2 S levels in the brain are unchanged in HO-2-null mice compared with WT mice (Fig. 3E), possibly due to compensatory changes in endogenous H 2 S production from other enzymes in the transsulfuration pathway (27).…”
Section: Discussionsupporting
confidence: 81%
“…This notion is consistent with previous studies indicating that pharmacologic inhibition of HO increases basal O 2 consumption in the liver (52) and that an increase in endogenous CO, by enzyme induction inhibits cellular respiration through its inhibitory effect on cytochrome c oxidase (53). H 2 S also might modulate mitochondrial respiration through reversible inhibition of cytochrome c oxidase (54); however, at least in the present study, basal H 2 S levels in the brain are unchanged in HO-2-null mice compared with WT mice (Fig. 3E), possibly due to compensatory changes in endogenous H 2 S production from other enzymes in the transsulfuration pathway (27).…”
Section: Discussionsupporting
confidence: 81%
“…Using exogenous H 2 S, we demonstrated that it promotes H 2 O 2 killing by specifically damaging heme-containing proteins, especially the CAT KatB, even though it is able to induce the protective OxyR regulon, as described in other bacterial species (3). Such an inhibitory effect on heme-containing proteins such as Cco (mitochondrial aa 3 type), myoglobin, and hemoglobin by H 2 S is well documented in eukaryotes (44)(45)(46). In general, the reaction between these proteins and H 2 S induced modification of the heme component, reversibly inhibiting activity (46,47).…”
Section: Discussionmentioning
confidence: 82%
“…Oxygen consumption is obligatory during H 2 S metabolism, and 1 mol of oxygen is consumed for every mol of H 2 S oxidized along the electron transport chain (53 (82). It is important to note that sulfide oxidation in the mitochondria appears to take priority over oxidation of other carbon-based substrates, ensuring its efficient removal (24). This plus the fact that the capacity of cells to oxidize sulfide appears to be considerably greater than the estimated rate of sulfide production (24) ensures that intracellular H 2 S concentrations are very low.…”
Section: Metabolism (Inactivation)mentioning
confidence: 99%